Bullying and its relation to parental treatment style (Journal Of Educational and Psychological Researches, 2012)
The current research aims to know the relationship between bullying and parental treatment. (200) pupils were selected randomly from the fifth and sixth grades of primary schools. Two instruments were used. The first was to measure bullying and it included 19 items. To measure parental treatment, the researchers adopted (Aletaby 2001) scale.Statistical analysis showed that correlation between bullying , wiggle and Firm treatment style was positive Statistically significant .Bulling was correlated negatively with (neglect, careless, and Authoritarian treatment style.